Dislocated quasi-b-metric spaces and fixed point theorems for cyclic weakly contractions - Cholatis Suanoom (2018)
© 2016 All rights reserved. In this paper, we introduce the notions of type dqb-cyclic-weak Banach contraction, dqb-cyclic- Φ - contraction and derive the existence of fixed point theorems on dislocated quasi-b-metric spaces. Our main theorem extends and unifies existing results in the recent literature.